All-Cause and Cause-Specific Risk of Emergency Transport Attributable to Temperature: A Nationwide Study. Issue 51 (December 2015) - Onozuka, Daisuke; Hagihara, Akihito
Abstract : Abstract: Although several studies have estimated the associations between mortality or morbidity and extreme temperatures in terms of relative risk, few studies have investigated the risk of emergency transport attributable to the whole temperature range nationwide. We acquired data on daily emergency ambulance dispatches in all 47 prefectures of Japan from 2007 to 2010. We examined the relationship between emergency transport and temperature for each prefecture using a Poisson regression model in a distributed lag nonlinear model with adjustment for time trends. A random-effect multivariate meta-analysis was then applied to pool the estimates at the national level. Attributable morbidity was calculated for high and low temperatures, which were defined as those above or below the optimum temperature (ie, the minimum morbidity temperature) and for moderate and also extreme temperatures, which were defined using cutoffs at the 2.5th and 97.5th temperature percentiles. A total of 15, 868, 086 cases of emergency transport met the inclusion criteria. The emergency transport was attributable to nonoptimal temperature. The median minimum morbidity percentile was in the 79th percentile for all causes, the 96th percentile for cardiovascular disease, and the 92th percentile for respiratory disease. The fraction attributable to low temperature was 6.94% (95% eCI: 5.93–7.70) for all causes, 17.93% (95% eCI: 16.10–19.25) for cardiovascular disease, and 12.19% (95% eCI: 9.90–13.66) for respiratory disease, whereas the fraction attributable to high temperature was small (all causes = 1.01%, 95% eCI: 0.90–1.11; cardiovascular disease = 0.10%, 95% eCI: 0.04–0.14; respiratory disease = 0.29%, 95% eCI: 0.07–0.50). The all-cause morbidity risk that was attributable to temperature was related to moderate cold, with an overall estimate of 6.41% (95% eCI: 5.47–7.20). Extreme temperatures were responsible for a small fraction, which corresponded to 0.57% (95% eCI: 0.50–0.62) for extreme low temperature and 0.29% (95% eCI: 0.26–0.32) for extreme high temperature. The same trends were observed for cardiovascular and respiratory diseases. The majority of temperature-related emergency transport burden was attributable to lower temperature. The effect of extremely high or low temperatures was markedly lower than that attributable to moderately nonoptimal temperatures. Abstract : Supplemental Digital Content is available in the text